ANTIMICROBIAL FINISHING ON 100% COTTON FABRIC BY USING STEM OF ABUTILON INDICUM - M, Jayakumari.; R, Divya . (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Abutilon indicum (Linn) family Malvaceae, commonly known as Atibala is an importantmedicinal plant. The whole plant as well as specific part such as root, leaves, and flowers is usedto treat various healthy aliments skin treatment. It is found as a weed in sub Himalayan tracts,hills up to 1200m and in hotter parts of india. The plant is found to possess immunodulatory,anticonvulsant, larvicidal, lipid lowering, diuretic, and anti-ulcer activity. The plant containsantimicrobial activity in nature.The stem of the plant was shade dried and powdered to test thepresence of antimicrobial activity .This study reveals the effect of antimicrobial activity and antifungal activity of theabutilon indicum plant extract on cotton fabric.